EKSKLUSI SOSIAL: PERSPEKTIF BARU UNTUK MEMAHAMI DEPRIVASI DAN KEMISKINAN - Syahra, Rusdi (Jurnal Masyarakat dan Budaya, 2010)
This article is a brief account on the introduction and development of the concept of social exclusion in the intellectual discourse and national policy, primarily in the western countries. The concept, which is multidimensional in nature, is a new paradigm that seeks to explain deprivation and poverty in the light of asymmetric relations between the exclusive groups who command a variety of resources and the ones who are made disadvantageous. The concept, first introduced in France in 1974 to explain the erosion of solidarity among the French society, has sinced been adopted in many western countries and developing countries alike, to explain the causes social discontents of the excluded. Despite its relatively successful application as policy guidelines to minimize deprivation in many European countries, the concept has not yet been widely known in Indonesia. While, many forms of social exclusion have been part of social and cultural life in the archipelago since the historical past, in fact, the concept of social exclusion as a scientific approach has not been instrumental in explaining factors leading to the disadvantages and impoverishment of the deprivative groups. While another concept, social capital, has entered intellectual discourse since many years and has been used by many international assistance agencies as an approach in their development programs and projects, only a limited number of scientific papers on social exclusion have been found to address this issue. Keywords: Social exclusion, paradigm, deprivation, poverty, social capital